"Uso de videojuegos por internet y su relación con el grado de agresividad en adolescentes. Distrito La Esperanza-Trujillo, 2006" - Calle Morales, María Carolina (2006)
The present Study of investigacion quantitative prospectivo, of correlational descriptive type, was made in adolescents of 10 to 19 years old, of the District La Esperanza, during the months December, 2005 to November , 2006, with the purpose of determining the existent relations between the Videogames by Internet and the degree of Aggressiveness in the Adolescents. The sample was conformed by 149 adolescents between the ages of 10 to 19 years of both sexes. For the data collection used two instruments: Format of survey of the use of Videogames in Internet and the Test of Aggressiveness AGA. The data were process following a pattern of manual tabulation and statistical by means of the test of independence of square Chi criteria, the results were presented in pictures of simple and double entrance. Reaching the following conclusions: The frequency whereupon the adolescents make use of the videogames by Internet is mainly (40,3 porcent) every day, with a duration of 1 to 2 hours (60,4 porcent), preferring videogames of violent content (62,4 porcent). Exists sighly significant relation between the variables frequency and duration of the use of videogames by Internet and the degree of aggressiveness of the adolescents exists highly. Also, exists highly significant relation between the type of videogames exists and the aggressiveness degree, being observed the group of adolescents who prefer the videogames of violent type presented degree of moderate and high aggressiveness (51,6 porcent and 9,7 porcent respectively).